Perencanaan Rancangan Anggaran Biaya Pembangunan Asrama Putri di Pesantren At-Tauhid - yulianti, dimitri; Sari, Anggi Nidya; Lubis, Lega Reskita; Marlina, Ayu; Wardhan, Dyah Utari Yusa; Homzah, Ozkar Firdausi; Suryan, Viktor (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2024)
Education is something important for human life. Islamic boarding schools are religious, educational facilities, so complete facilities are needed to meet student's academic and non-academic needs. Costs play an essential role in project implementation. Therefore, cost budget planning must be designed and prepared well based on an estimation concept to produce precise and economical cost estimates. The Cost Budget Plan calculates the costs required to implement the project to determine the price of materials and wages, as well as other costs required in implementing the project in detail. The Girls' Dormitory Construction Project at the At-Tauhid Sriwijaya Islamic Boarding School is one of the construction projects whose value has experienced a relatively high rate of increase compared to civil construction and other unique construction. This activity was carried out to improve services at the At-Tauhid Islamic Boarding School because the number of students is increasing yearly. By providing an estimate of the cost of building a girls' dormitory at the AtTauhid Islamic boarding school. This aims to make it easier for the At-Tauhid Islamic boarding school to calculate the draft budget for constructing the girls' dormitory. The budget planning for the construction of the girls' dormitory at At-Tauhid was carried out based on the plan drawings that had been made previously. The community service method in this activity uses the Service Learning method. This activity's result is to  facilitate the plan to build a girls' dormitory at the At-Tauhid Islamic Boarding School so that it can be realizedmore quickly. This cost budget plan is made with efficient and effective cost estimates. In order to increase the effectiveness of community service, further research suggestions are actors that affect the cost of building a girls' dormitory, as well as developing a model that is more effective in estimating the cost of building a girls' dormitory.